HLA-DR15-specific inhibition attenuates autoreactivity to the Goodpasture antigen. (September 2019) - Huynh, Megan; Eggenhuizen, Peter J.; Olson, Gary L.; Rao, N. Bhaskara; Self, Christopher R.; Sun, Yanjun; Holdsworth, Stephen R.; Kitching, A. Richard; Ooi, Joshua D.
Abstract: Goodpasture's disease manifests as rapidly progressive glomerulonephritis. Current immunosuppressive treatments do not specifically target the pathological immune response and have significant side effects. Like most autoimmune diseases, the strongest genetic association is with the HLA alleles. Inheritance of HLA-DR15 confers susceptibility, and structure-function studies have shown that HLA-DR15 plays a causative role in activating autoreactive pro-inflammatory T cells. Thus, specific inhibition of HLA-DR15 would provide a targeted therapeutic approach. We hypothesised that PV-267, an HLA-DR15-specific inhibitor, would effectively block HLA-DR15 presentation of the dominant epitope, attenuate the activation of autoreactive T cells, and limit disease. Using humanised HLA-DR15 transgenic mice, α3135-145 -specific, pro-inflammatory T cell recall responses were measured using IFN-γ and IL-17A ELISPOTs and by proliferation assay. To determine if PV-267 could limit disease, experimental autoimmune anti-GBM glomerulonephritis was induced in HLA-DR15 transgenic mice (on an Fcgr2b −/- background), and functional and histological disease endpoints were measured. PV-267 effectively inhibited α3135-145 -specific immune responses and disease development. Mice treated prior to immunization with α3135-145 had reduced α3135-145 -specific recall responses, and limited disease by albuminuria, histological glomerular injury, IgG deposition, and inflammatory cell infiltrates. PV-267 treatment commencing after the onset of active anti-α3(IV)NC1 autoimmunity attenuated functional and histological renal injury. When treatment was administered after disease was established, PV-267 limited the severity of histological injury. In conclusion, HLA-DR15 inhibition attenuates α3(IV)NC1-specific pro-inflammatory responses and could be used as an adjunct therapy for anti-GBM disease. Highlights: PV-267 inhibits HLA-DR15 and blocks α3135-145 -specific responses. HLA-DR15 inhibition protects mice from autoimmune anti-GBM glomerulonephritis. Blocking HLA-DR15 after autoimmunity induction stops disease development in mice. Treating renal injury with HLA-DR15 inhibition limits disease severity in mice.